Sediment deposition characteristics of urban concrete drains in Kuching City, Sarawak, Malaysia - Charles, Hin Joo Bong; Tze, Liang Lau; Aminuddin, Ab. Ghani (Universiti Malaysia Sarawak, UNIMAS, 2011)
Sediment deposition in drains has been found to be one of the major causes of flooding in urban areas. In order to design an effective removal mechanism, an understanding of the characteristics of the sediment deposition is needed. This paper highlights the results of sediment size characteristics analysis done on sediment samples collected from concrete drains in Kuching city, Sarawak, Malaysia. A total of 30 sediment samples from 10 urban locations (4 residential areas, 5 commercial areas and 1 industrial area) were collected and subjected to sieve analysis. Results from sieve analysis had shown that the major component of the sediment is sand with an average percentage of 68.8%, followed by gravel with average percentage of 30.4% and silt and clay as the minor component with an average percentage of 0.8%. Of the 30 samples, 7 samples show bimodal characteristics while 23 samples show unimodal characteristics. 14 out of the 23 unimodal samples had shown a non uniform distribution with the tendency to skew to the coarser grain size. Due to this, the conventional use of median grain size d50 as the effective size for the sediment samples might not be a good representation for the sediment distribution. Further statistical analysis in this paper had suggested that the mode grain size is a much better representative grain size due to its stability when compared to median and mean size. Thus, a much better representative size for the sediment samples from Kuching urban areas would be the mode size (in this case is d45). An analysis on drain characteristics had shown that trapezoidal shape drain tends to have higher blockage percentage due to sediment deposition when compared to rectangular shape drain.